Microfluidic Technology for the Production of Hybrid Nanomedicines - Ilaria Ottonelli; Jason Thomas Duskey; Arianna Rinaldi; Maria Vittoria Grazioli; Irene Parmeggiani; Maria Angela Vandelli; Leon Z. Wang; Robert K. Prud'homme; Giovanni Tosi; Barbara Ruozi (MDPI AG, 2021)
Microfluidic technologies have recently been applied as innovative methods for the production of a variety of nanomedicines (NMeds), demonstrating their potential on a global scale. The capacity to precisely control variables, such as the flow rate ratio, temperature, total flow rate, etc., allows for greater tunability of the NMed systems that are more standardized and automated than the ones obtained by well-known benchtop protocols. However, it is a crucial aspect to be able to obtain NMeds with the same characteristics of the previously optimized ones. In this study, we focused on the transfer of a production protocol for hybrid NMeds (H-NMeds) consisting of PLGA, Cholesterol, and Pluronic® F68 from a benchtop nanoprecipitation method to a microfluidic device. For this aim, we modified parameters such as the flow rate ratio, the concentration of core materials in the organic phase, and the ratio between PLGA and Cholesterol in the feeding organic phase. Outputs analysed were the chemico-physical properties, such as size, PDI, and surface charge, the composition in terms of %Cholesterol and residual %Pluronic® F68, their stability to lyophilization, and the morphology via atomic force and electron microscopy. On the basis of the results, even if microfluidic technology is one of the unique procedures to obtain industrial production of NMeds, we demonstrated that the translation from a benchtop method to a microfluidic one is not a simple transfer of already established parameters, with several variables to be taken into account and to be optimized.